Stretching and deep and superficial massage do not influence blood lactate levels after heavy-intensity cycle exercise - Cè, E.; Limonta, E.; Maggioni, M. A.; Rampichini, S.; Veicsteinas, A.; Esposito, F. (Journal of Sports Sciences, 2013)
The study aimed to assess the role of deep and superficial massage and passive stretching recovery on blood lactate concentration ([La-]) kinetics after a fatiguing exercise compared to active and passive recovery. Nine participants (age 23 ± 1 years; stature 1.76 ± 0.02 m; body mass 74 ± 4 kg) performed on five occasions an 8-min fatiguing exercise at 90% of maximum oxygen uptake, followed by five different 10-min interventions in random order: passive and active recovery, deep and superficial massage and stretching. Interventions were followed by 1 hour of recovery. Throughout each session, maximum voluntary contraction (MVC) of the knee extensor muscles, [La-], cardiorespiratory and metabolic variables were determined. Electromyographic signal (EMG) from the quadriceps muscles was also recorded. At the end of the fatiguing exercise, [La-], MVC, EMG amplitude, and metabolic and cardiorespiratory parameters were similar among conditions. During intervention administration, [La-] was lower and metabolic and cardiorespiratory parameters were higher in active recovery compared to the other modalities (P < 0.05). Stretching and deep and superficial massage did not alter [La-] kinetics compared to passive recovery. These findings indicate that the pressure exerted during massage administration and stretching manoeuvres did not play a significant role on post-exercise blood La- levels.